Apatia na doença de alzheimer: Contribuição para uma visão clínica da progressão da demência - Stella, Florindo [UNESP]; de Andrade, Larissa Pires [UNESP]; Vital, Thays Martins [UNESP]; de Melo Coelho, Flávia Gomes [UNESP]; Nascimento, Carla Manuela Crispim [UNESP]; Hernández, Salma Stephany Soleman [UNESP] (My University, 2010)
In addition to cognitive impairment, apathy is increasingly recognized as an important neuropsychiatric syndrome in Alzheimer's disease (AD). Aims: To identify the relationship between dementia severity and apathy levels, and to discuss the association of this condition with other psychopathological manifestations in AD patients. Methods: This study involved 15 AD patients (mean age: 77 years; schooling: 4.9 years), with mild, moderate and severe dementia, living in Rio Claro S P, Brazil. Procedures included evaluation of cognitive status by the Mini-Mental State Examination, Clinical Dementia Rating, and Global Deterioration Scale. Apathy syndrome was assessed by the Apathy Evaluation Scale and Neuropsychiatric Inventory (NPI-apathy domain). Other psychopathological manifestations such as depression were also considered. Results: Patients with more severe dementia presented higher levels of apathy, reinforcing the hypothesis that apathy severity aggravates as the disease progresses. Using the Spearman coefficient correlation an association was identified between the MMSE and Apathy Evaluation Scale (r=0.63; p=0.01), and also between the MMSE and NPI-apathy domain (r=0.81; p=0.01). Associations were also found between the Global Deterioration Scale and Apathy Evaluation Scale (r=0.58; p=0.02), and between the Global Deterioration Scale and NPI-apathy domain (r=0.81; p=0.01). Conclusions: Apathy is a distinct syndrome among patients with AD and increases with global deterioration.
Apathy in alzheimer's disease: Contribution to a clinical view on progression of dementia
Keywords: Alzheimer's disease; Apathy; Disease progression